Pharmacokinetics of Benzathine Penicillin G - Saraya, Sumarn; Saraya, Arunee; Thanasarnsombut, Sirichai (Journal of Basic and Applied Pharmacology, 2015)
Benzathine penicillin G kinetics were studied in patients with rheumatic heart disease after single intramuscular injection of 1.2 million units of benzathine penicillin G. Penicillin G plasma concentrations were measured by microbiological assay and fitted by least squares linear regression analysis to a monoexponential equation. Calculated elimination half- life (t0.5) and rate constant (kel) were 16.5 ± 3.8 day and 0.0532 ± 0.011 day-1, respectively. Body clearance (Cl) was 570 ± 50.9 litre.day-1and the area under the curve (AUC0 to ∞) was 1.66 ± 0.19 μg. ml-1. day. The result shows that monthly intramuscular injection for rheumatic fever prophylaxis may be adequate. Note: Pharmacokinetic parameters were shown as mean ± sem.